Analisis Faktor-Faktor yang Memengaruhi Penerapan Standar Akuntansi Pemerintah pada Kantor Wilayah Kementerian Hukum dan HAM Sumatera Selatan - Eriza Khosakiyah; Vhika Meiriasari; Andini Utari Putri (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
This study aims to investigate the influence of the quality of human resources, government accounting system, and political process on the application of government accounting standards at the Ministry of Law and Human Rights of South Sumatra. The population was all 152 employees at the Ministry of Law and Human Rights. Data were collected through questionnaires to 40 respondents and analysed using multiple linear regression on SPSS V25. The results prove that partially the quality of human resources and the government accounting system affects the application of government accounting standards. Conversely, the political process has no effect on the application of government accounting standards. Simultaneously, the quality of human resources, government accounting systems, and political processes have an effect on the application of government accounting standards.